Pengaruh Operating Cash Flow dan Revenue Growth Terhadap Financial Distress pada Perusahaan Konstruksi Bangunan di BEI Periode 2021-2024 - Intan Ayu Nuraini; Aisyaturrahmi (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyze the effect of operating cash flow and revenue growth on financial distress in building construction companies listed on the Indonesia Stock Exchange for the 2021–2024 period. The study employed a quantitative approach utilizing secondary data in the form of annual financial reports. The sample was determined using a purposive sampling technique, resulting in 26 companies with a total of 104 observational data. Data analysis was conducted in stages using descriptive statistics, classical assumption tests, and panel data regression analysis to examine the relationship between independent variables and financial distress. The results showed that operating cash flow had no significant effect on financial distress. This finding indicates that operating cash flow is not able to directly reflect financial distress, particularly in construction companies characterized by long-term project cycles and large capital requirements. Conversely, revenue growth had a significant negative effect on financial distress, indicating that increased revenue growth can reduce the risk of financial distress for companies. The control variables used in the study also showed an effect on financial distress. The implications of this study provide input for management and investors that revenue growth indicators are more relevant in assessing potential financial distress than operating cash flow in the construction sector.